John Bell (1796-1868) - Coates, Kenneth S. (ARCTIC, 1986)
John Bell, discoverer of the Yukon River and associate of Drs. John Richardson and John Rae in the Franklin search expedition of 1847-1849, represented the classic blend of fur trader and explorer. His contributions to the expansion of the Company's trade in the far northwest and to the cause of arctic exploration have gone largely unnoticed, due in some measure to his unassuming and modest character. . His northern career began in 1824 when, as an officer of the reorganized Hudson's Bay Company, he was transferred to the Mackenzie District. In 1837, Thomas Simpson and Peter Warren Dease had discovered the Colville River on the arctic coast. Anxious to exploit this find, Governor Simpson ordered that John Bell, by now an experienced northern trader, attempt to locate an overland route joining the Mackenzie and the Colville. In 1839, Bell travelled along the lower reaches of the Peel River, looking for a breach in the mountains that would take him west. Though he did not immediately succeed, his reports of the excellent prospects for trade encouraged the Company to establish a trading post. Bell opened Peel's River Post, later renamed Fort McPherson, in 1840. On Governor Simpson's directions, he also continued his explorations of the lands west of the Mackenzie. . The Hudson's Bay Company took an active part in the attempt to locate the lost Franklin expedition. In 1847, Governor Simpson assigned John Bell to assist with an expedition, led by Drs. John Richardson and John Rae, that searched the coast between the Mackenzie and Coppermine rivers. Bell's primary responsibility was to provide logistic support for the venture; during 1848, for example, Bell built Fort Confidence on Great Bear Lake as a wintering station for the expedition. At the completion of Richardson and Rae's journey, Bell returned to his fur trade duties and was assigned to Fort Liard. . Many northern explorers rushed descriptions of their travels into print, anxious to share news of their discoveries and to bask in the fame due a northern ...